AUGMENTED REALITY, SEBUAH TREN DAN NILAI DALAM PERKEMBANGAN INDUSTRI PARIWISATA - I Putu Sagita Jaya Utama; I Made Arsa Wiguna (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2019)
The use of modern technology is a necessity for many destinations to remain competitive and attractive to modern tourists. A form of new technology that is increasingly being used in public spaces is virtual reality and augmented reality (AR). How AR plays a role in the development of the tourism industry, so that it becomes a trend and value, is a reality that explored with a qualitative approach and a review of some relevant literature. The results of the study found that Augmented Reality is very instrumental in projecting additional information about attractions, accessibility and amenities in the tourism environment to be closer to everyone.